Indentifikasi Kandungan Zink (Zn), Besi (Fe) dan Escherichia Coli Pada Sumber Air Bersih Dengan Analisis Spasial Ecological Risk Assessment Di Desa Tungka Kecamatan Enrekang Kabupaten Enrekang - Sudarman, Dirman; Baharuddin, Alfina; Muhammad Ikhtiar; Haeruddin; Reza Aril Ahri; Sitti Fatimah (Journal of Aafiyah Health Research (JAHR), 2021)
Background: Based on WHO data, it is known that nearly 40% of deadly diseases in all countries are related to poor water quality, there are around 2.6 million people worldwide die each year due to diseases caused by dirty water or water that does not meet health requirements. Zinc and Iron are essential mineral substances needed by the body, but in excess amounts will cause poisoning. This deficiency causes growth disorders, affects sexual maturation, susceptibility to infections, diarrhea, and annually causes the death of approximately 800,000 children worldwide. The second most common cause of diarrhea after rotavirus is infection due to the bacteria Escherichia coli, the annual incidence of diarrhea in children is estimated at 2.5 billion, and more than half of it is found in Africa and South Asia and the consequences of this disease are more severe and deadly. Globally every year this disease causes the death of children under five of 1.6 million. Objective: The aim of this study is to identify to map the Zinc (Zn), Iron (Fe) and Escherichia Coli Content in Clean Water Sources with a Spatial Ecological Risk Assessment Analysis in Tungka Village Enrekang District, Enrekang Regency. Methods: This research is descriptive observational, to identify and map the content of zinc (Zn), iron (Fe) and Escherichia Coli in clean water sources in Tungka Village, Enrekang District, Enrekang Regency and calculate the ecological risk assessment. The research design used an ecological risk assessment approach. Sampling was carried out at 6 different points. Results: The results obtained in this study, the amount of zinc content still met the quality standard requirements, namely <3 mg / l of the Republic of Indonesia Minister of Health Regulation No.492 / Menkes / Per / IV / 2010 for zinc content, namely 3 mg / l, with a risk index ecological potential, namely PERI = ∑E_r ^ i (0.831) <150 with low risk category. The iron content is still below the standard, namely <0.3 mg / l, the standard Permenkes RI No.492 / Menkes / Per / IV / 2010 for iron content is 0.3 mg / l, with a potential ecological risk index of PERI = ∑E_r ^ i (0.1797) <150 with low risk category. Meanwhile, the content of escerchia coli does not meet the requirements, namely> 0CFU / ml quality standards, namely the Republic of Indonesia Minister of Health Regulation No.492 / Menkes / Per / IV / 2010 for the content of E. coli, namely 0 CFU / ml. With a risk index, namely PERI = ∑E_r ^ i (46,7.10-6)> 1.10-6 with a very high risk category